(3JcfhdhLjG hbhGdH GdMbf (B/s - (3NdjaI, SdjeGfs ((3OeTb (B:s (3OGQ OeTb ddWHGYI hGdfTQ hGdJhRjY,s, 1996)
(3eONd Edi JcfhdhLjG hbhGdH GdMbf(B-(3eONd Edi JcfhdhLjG GdMbf(B-(3Gdeaghe GdJbdjOj ddMbf(B-(3Gdeaghe GdMOjK ddMbf(B-(3JbfjGJ MOjKI(B-(3GdOQGSI GdJcfhdhLjI ddefJL(B-(3cja JUfY bGdH Mbf(B.s
(3jJhGaQ HGdecJHI GdLRA GdKGdK(B.s
(3jTJed Ydi bGFeI eUWdMGJ(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3UfGYI hJLGQI GdHdGSJjcs; (3GdHdGSJjcs -- (3VHW LhOIs; (3GdHdGSJjcs -- (3LhGfH UMjIs